(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2024)
Emotional intelligence is examined as a critical component of effective school leadership. This study investigates how emotional intelligence skills, such as self-awareness, empathy, and social skills, contribute to successful leadership practices and positive school climates.